Chemical Profiling of Scoparia dulcis L. Leaf Ethanol Extract and In Silico Antiaging 2Y9X Inhibitor Study - Anjani Fadia Putri; Tukiran Tukiran (Jurnal Pijar MIPA, 2026)
The intensity of UV radiation that is quite high in the tropics can make the skin age quickly, such as wrinkles, dry, dull skin, or dark spots. In Indonesia, it turns out that 76% of women experience premature aging in this way. The cause is exposure to UVA and UVB radiation, which triggers the production of Reactive Oxygen Species (ROS). Many local plants have been researched for anti-aging, but no one has discussed the anti-aging activity of Scoparia dulcis L. Previous research indicates that Scoparia dulcis L. leaves exhibit antibacterial, antimicrobial, antioxidant, anti-inflammatory, and antidiabetic effects. Therefore, this study aimed to identify potential anti-aging compounds in the ethanol extract of Scoparia dulcis L. leaves as inhibitors of tyrosinase enzyme (PDB ID: 2Y9X), which plays a role in melanin production. Plant material was macerated to preserve flavonoid compounds. Chemical profiling of the extract was analyzed using LC-MS, which identified 104 secondary metabolite compounds. Then, use an in silico approach through molecular docking with AutoDock Vina to evaluate anti-aging compounds in the ethanol extract of Scoparia dulcis L. leaves. The docking results indicated that six compounds showed promising inhibitory potential, with binding affinities better than that of the positive control (-6.0 kcal/mol). These compounds were vanillic acid (-6.2 kcal/mol), caffeic acid (-6.0 kcal/mol), scopoletin (-6.4 kcal/mol), scoparone (-6.2 kcal/mol), jasmonic acid (-6.2 kcal/mol), and budlein A (-6.2 kcal/mol). The six compounds were also analyzed again using Lipinski's Rule of Five so that they could be used as a reference for further experiments for oral drugs. As a result, all of six compounds met that rule and had a smaller bond affinity value than the positive control.